Energy Trading in Local Electricity Markets with Renewables- A Contract Theoretic Approach - Amin, Uzma; Hossain, J; Tushar, W; Mahmud, K (IEEE, 2020)
This paper introduces a new contract-theoretic framework to tackle this challenge by designing optimal contracts for ESs. A dynamic pricing scheme is developed that the aggregator can utilize to incentivize the ESs to contribute to both baseload and peak load demands according to their categories. An algorithm is proposed that can be implemented in a distributed manner by trading partners to enable energy trading. It is shown that the trading strategy under a baseload scenario is feasible, and the aggregator only needs to consider the per unit generation cost of ESs to decide on its strategy. The trading strategy for a peak load scenario, however, is complex and requires consideration of different factors such as variations in the wholesale price and its effect on the selling price of ESs, and the uncertainty of RESs. Simulation results demonstrate the effectiveness of the proposed scheme for energy trading in local electricity market